Podcast pada Kalangan Mahasiswa dapat mendorong kreativitas dalam pengembangan soft Skill - Shofa Lutfiah Fitri; Alissa Eka Rahmawati; Angel Imannuel; Baiti Jannati; Taufik Hidayat (Jurnal Pengabdian Masyarakat Sultan Indonesia, 2024)
Being a student is a phase where self-development is inevitable, where students are often asked for many things at the same time so that many students become stressed and do not have a transition that is also a good self-development tool. On the other hand, a podcast cannot be underestimated because podcasts can be a bridge for students to become better, both in terms of mental and self-development. Listening to podcasts cannot be underestimated, because students are invited to reflect on everyday life stories in a funny and informal way. In addition, they can also foster a sense of empathy for others through stories of experiences from other people, they can also appreciate diversity more. Sharing stories with podcasts is also certainly very beneficial for students because it makes them feel more valued and heard and increases students' own self-confidence because students are able to face their shyness and or self-doubt.